Variability and change in the hydro-climate and water resources of Iran over a recent 30-year period - Moshir Panahi, Davood (Sci Rep, 2020)
Comprehensive assessment of hydro-climatic variations and change trends is essential for understanding, mitigating, and adapting to key water resource changes in different parts of the world. We performed such an assessment on Iran, as representative of an arid/semi-arid and geopolitically important world region. We acquired and calculated data time series of surface temperature (T), precipitation (P), runoff (R), evapotranspiration (ET), and water storage change (DS), to determine their status and changes in and among the 30 main hydrological basins in Iran over the period 1986–2016. From 1986–2000 to 2001–2016, the country warmed, P mostly decreased and R even more so, while water storage was depleted (DS < 0) and ET increased in some basins. Overall, the extra water provided from primarily groundwater depletion has fed and kept ET at levels beyond those sustained by the annually renewable water input from P. This indicates unsustainable use of water for maintaining and expanding human activities, such as irrigated agriculture, in this part of the world.